A Parasitoid Puzzle: Phylogenomics, Total-evidence Dating, and the Role of Gondwanan Vicariance in the Diversification of Labeninae (Hymenoptera, Ichneumonidae). Issue 5 (21st September 2022) - Santos, Bernardo F; Sandoval, Marissa; Spasojevic, Tamara; Giannotta, Madalene M; Brady, Seán G
Abstract: Biogeographic patterns in the Southern Hemisphere have largely been attributed to vicariant processes, but recent studies have challenged some of the classic examples of this paradigm. The parasitoid wasp subfamily Labeninae has been hypothesized to have a Gondwanan origin, but the lack of divergence dating analysis and the discovery of a putative labenine fossil in Europe pose a challenge to that idea. Here we used a combination of phylogenomics, divergence dating and event-based biogeographical inference to test whether Gondwanan vicariance may explain the distribution patterns of Labeninae. Data from genomic ultraconserved elements were used to infer the phylogeny of Labeninae with 54 species from 9 genera and a broad selection of 99 outgroup taxa. Total-evidence divergence dating places the origin of Labeninae at around 146 mya, which is consistent with a Gondwanan origin but predates the full separation of Africa and South America. The results suggest a path for biotic exchange between South America and Australia potentially through Antarctica, until at least 49 million years ago. Total-evidence analysis places the fossil Trigonator macrocheirus Spasojevic et al. firmly inside crown-group Labeninae, suggesting that labenine distribution range at some point during the Eocene surpassed the boundaries of Gondwanaland. Biogeographic inference also indicates that North American groups represent more recent range expansions that nonetheless occurred before the formation of the Isthmus of Panama land bridge. These conclusions point to a more complex scenario than previously expected for Labeninae biogeography.